Analisis Terhambatnya Pencairan Pembiayaan Murabahah Nasabah Pensiunan Perkebunan pada PT BPRS Amanah Bangsa - Hana Nafisah; Ahmad Perdana Indra (Masyarakat Ekonomi Syariah Bogor, 2023)
The Amanah Bangsa Sharia People's Financing Bank (BPRS) located in Kab. Simalungun is one of the financial institutions that has a murabahah financing program for employees who have retired from plantations. The installment payment system is adjusted to the amount of income received by the customer. However, there are still customers who experience delays in disbursing murabahah funds due to the lack of complete administrative data. This study aims to determine the completeness of the data that must be met by customers in order to avoid delays in the disbursement process and to know the procedures for disbursing murabahah financing. The results showed that this personal data file can be applied in accordance with what has been set by the BPRS Amanah Bangsa Kab. Simalungun to overcome obstacles such as the delay in the process of disbursing murabahah financing. By completing the personal data file, following this structured mechanism in order to expedite the process of disbursing murabahah financing. Keyword : BPRS Amanah Bangsa, Financing, Requirements